Beta-Lactam-beta-lactamase-inhibitor combinations are active in experimental endocarditis caused by beta-lactamase-producing oxacillin-resistant staphylococci. - Hirano, L (1991)
Optimal therapeutic strategies for serious infections caused by borderline and heterotypic oxacillin-resistant Staphylococcus aureus (BORSA and ORSA) strains have not been fully characterized. Recent evidence suggests that the dominant penicillin-binding protein of ORSA strains (PBP 2a) shows good affinity for ampicillin and that these strains commonly produce beta-lactamase. Therefore, we compared the in vivo efficacy of the combination of ampicillin plus sulbactam with that of vancomycin against ORSA strains. Also, the moderate resistance of BORSA strains appears to be attributable mainly to the hyperproduction of beta-lactamase. Therefore, we also studied the in vivo efficacy of ampicillin plus sulbactam against such organisms. Experimental aortic endocarditis was induced in rabbits by the following three strains: beta-lactamase-producing BORSA strain VP-986, beta-lactamase-producing ORSA strain 67-0, and its beta-lactamase-negative clone. In animals with BORSA endocarditis, ampicillin plus sulbactam and oxacillin were highly effective in reducing mean intravegetation bacterial densities, with each being significantly better than either ampicillin alone or no therapy. In animals with endocarditis caused by the beta-lactamase-producing ORSA strain, ampicillin plus sulbactam was significantly better at reducing mean vegetation bacterial densities than the other regimens. For endocarditis caused by the beta-lactamase-negative ORSA clone, ampicillin was better than vancomycin in reducing mean intravegetation bacterial densities. These data show that infections caused by beta-lactamase-producing BORSA strains respond therapeutically in a manner similar to that of infections caused by oxacillin-susceptible strains, with both oxacillin and ampicillin plus sulbactam being highly efficacious. Moreover, high-dose ampicillin treatment strategies were effective in the therapy of ORSA endocarditis; this efficacy is presumably related to the relatively high affinity profile of this compound (compare with that of oxacillin) for the functionally dominant ORSA PBP 2a.